2002
DOI: 10.1073/pnas.042688499
|View full text |Cite
|
Sign up to set email alerts
|

The AF-1 activation-function of ERα may be dispensable to mediate the effect of estradiol on endothelial NO production in mice

Abstract: Two isoforms of estrogen receptor (ER) have been described: ER␣ and ER␤. The initial gene targeting of ER␣, consisting in the introduction of a Neo cassette in exon 1 [␣ERKO, hereafter called ER␣-Neo KO (knockout)], was reported in 1993. More recently, another mouse deficient in ER␣ because of the deletion of exon 2 (ER␣KO, hereafter called ER␣-⌬2 KO) was generated. In ovariectomized ER␣-wild-type mice, estradiol (E2) increases uterine weight and basal production of endothelial nitric oxide (NO). Both of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(173 citation statements)
references
References 46 publications
13
159
0
Order By: Relevance
“…[21][22][23] Specifically, expression of alternatively spliced transcripts lacking the AF-1 domain in ␣ERKO mice seems to mediate estrogen-induced endothelial NO production that is absent in the complete knockout. 24 These insights from mouse models suggest that mouse homologs of ⌬1a-hER␣-46 are sufficient to mediate the acute endothelial effects of estrogen and in principle support our observations of the functional effects of hER␣-46 in human endothelial cells, although the 46-kDa truncated ER␣ protein was not readily detected in mouse aortic lysates. 24 Additional studies are required to investigate possible roles for truncated ERs in mediating acute and transcriptional effects of estrogen in human pathophysiology.…”
Section: Figtree Et Al Truncated Er␣ Activates Enos 125supporting
confidence: 73%
“…[21][22][23] Specifically, expression of alternatively spliced transcripts lacking the AF-1 domain in ␣ERKO mice seems to mediate estrogen-induced endothelial NO production that is absent in the complete knockout. 24 These insights from mouse models suggest that mouse homologs of ⌬1a-hER␣-46 are sufficient to mediate the acute endothelial effects of estrogen and in principle support our observations of the functional effects of hER␣-46 in human endothelial cells, although the 46-kDa truncated ER␣ protein was not readily detected in mouse aortic lysates. 24 Additional studies are required to investigate possible roles for truncated ERs in mediating acute and transcriptional effects of estrogen in human pathophysiology.…”
Section: Figtree Et Al Truncated Er␣ Activates Enos 125supporting
confidence: 73%
“…While the E2 mRNA encodes only the first 41 amino acids of ER , the E1 mRNA encodes a potential ER isoform with a deletion in the B domain containing the AF-1 function. However, the corresponding E1 ER protein has been detected in ERKO tissues only recently (Pendaries et al 2002). The fact that the H222 antibody was originally used to analyze the presence of ER protein isoforms in ERKO uterine tissue by Western blot techniques (Couse et al 1995) might explain the failure to detect the E1 ER isoform which is expressed in ERKO at lower levels than ER in wild type mice.…”
Section: Discussionmentioning
confidence: 91%
“…This replacement would affect AF-1 transactivation function but not the DNA or ligand binding domain, which contains the AF-2 transactivation function. Such a protein isoform has recently been observed in mouse tissues (Pendaries et al 2002). The discovery of estrogen receptor (ER ) (Kuiper et al 1996) brought another potential explanation of the observed binding activity.…”
Section: Introductionmentioning
confidence: 99%
“…The IRF family members IRF-4 and IRF-8 play critical roles in the development and function of DCs (19,43,44). Although both factors have been shown to exhibit overlapping activity, they also possess DC subset-specific functions (43 (49). GM-CSF-dependent development of DCs depends not only on IRF-4, but also on other transcription factors, such as IRF-2, RelB, an Nf-kB family member, PU.1, Id2, C/EBP-a, C/EBP-b, IRF-8, and SpiB (20,44).…”
Section: Discussionmentioning
confidence: 99%